A ficção no diário de Anne Frank: do romance ao testemunho - e ao contrário - Lima, Ytalo dos Santos (2024)
The present dissertation aims to analyze the fictionality in the book "Diary of Anne Frank" based on its production and publication process. The research, of a bibliographical and documental character, seeks to understand fiction as mediation of the self and the other, in which in her continued writing Anne Frank resignified her own identity, perceiving herself while being an pariah and building experiences through the multiplicities of I’s present in her writings. The sources of the study comprise the versions of “Diary of Anne Frank”, consisting of her personal diary (version a), an autobiographical novel based on her diary (version b), a work published from 1991 onwards (version d), as well as short stories and an unfinished novel. The methodology employed is of a textual character and of a qualitative approach, varying the typology according to the specificity of the sources and of the objectives of analysis. The results indicate that in the publication process, in the exchange of characters’ names, an autobiographical novel was transformed into an autobiography of a testimonial character. The research contributes by bringing new meanings to the work of Anne Frank as well as to the debate about her representation in testimonial literature.